64-Slice computed tomography angiography in the diagnosis and assessment of coronary artery disease: systematic review and meta-analysis. Issue 11 (31st July 2008) - Mowatt, G; Cook, J A; Hillis, G S; Walker, S; Fraser, C; Jia, X; Waugh, N
Abstract : Context: Coronary artery disease (CAD) is a major cause of mortality and ill health. Objective: To assess whether 64-slice CT angiography might replace some coronary angiography (CA) for diagnosis and assessment of CAD. Data sources: Electronic databases, conference proceedings and reference lists of included studies. Study selection: Eligible studies compared 64-slice CT with a reference standard of CA in adults with suspected/known CAD, reporting sensitivity and specificity or true and false positives and negatives. Data extraction: Two reviewers independently extracted data from included studies. Results: Forty studies were included; 28 provided sufficient data for inclusion in the meta-analyses, all using a cut off point of ⩾50% stenosis to define significant CAD. In patient-based detection (n = 1286) 64-slice CT pooled sensitivity was 99% (95% credible interval (CrI) 97% to 99%), specificity 89% (95% CrI 83% to 94%), median positive predictive value (PPV) across studies 93% (range 64–100%) and negative predictive value (NPV) 100% (range 86–100%). In segment-based detection (n = 14 199) 64-slice CT pooled sensitivity was 90% (95% CrI 85% to 94%), specificity 97% (95% CrI 95% to 98%), median PPV across studies 76% (range 44–93%) and NPV 99% (range 95–100%). Conclusions: 64-Slice CT is highly sensitive for patient-based detection of CAD and has high NPV. An ability to rule out significant CAD means that it may have a role in the assessment of chest pain, particularly when the diagnosis remains uncertain despite clinical evaluation and simple non-invasive testing.